Disease modification and symptom relief in osteoarthritis using a mutated GCP‐2/CXCL6 chemokine. Issue 1 (12th December 2022) - Caxaria, Sara; Kouvatsos, Nikolaos; Eldridge, Suzanne E; Alvarez‐Fallas, Mario; Thorup, Anne‐Sophie; Cici, Daniela; Barawi, Aida; Arshed, Ammaarah; Strachan, Danielle; Carletti, Giulia; Huang, Xinying; Bharde, Sabah; et al.
Abstract: We showed that the chemokine receptor C‐X‐C Motif Chemokine Receptor 2 (CXCR2) is essential for cartilage homeostasis. Here, we reveal that the CXCR2 ligand granulocyte chemotactic protein 2 (GCP‐2) was expressed, during embryonic development, within the prospective permanent articular cartilage, but not in the epiphyseal cartilage destined to be replaced by bone. GCP‐2 expression was retained in adult articular cartilage. GCP‐2 loss‐of‐function inhibited extracellular matrix production. GCP‐2 treatment promoted chondrogenesis in vitro and in human cartilage organoids implanted in nude mice in vivo . To exploit the chondrogenic activity of GCP‐2, we disrupted its chemotactic activity, by mutagenizing a glycosaminoglycan binding sequence, which we hypothesized to be required for the formation of a GCP‐2 haptotactic gradient on endothelia. This mutated version (GCP‐2‐T) had reduced capacity to induce transendothelial migration in vitro and in vivo, without affecting downstream receptor signaling through AKT, and chondrogenic activity. Intra‐articular adenoviral overexpression of GCP‐2‐T, but not wild‐type GCP‐2, reduced pain and cartilage loss in instability‐induced osteoarthritis in mice. We suggest that GCP‐2‐T may be used for disease modification in osteoarthritis. Synopsis: Osteoarthritis, which is the most common cause of disability, leads to breakdown of the articular cartilage and causes joint pain and loss of mobility; however, we do not have a pharmacological treatment for arresting or reverting its course. The chemokine GCP‐2 is expressed within the articular cartilage where it supports extracellular matrix production and inhibits chondrocyte hypertrophy and cartilage mineralization. Mutagenesis of three lysines in GCP‐2 (GCP‐2‐T) disrupted its binding to glycosaminoglycans (e.g. on endothelium), reducing its induction of transendothelial migration of pro‐inflammatory leukocytes in vitro and in vivo . GCP‐2‐T retained the capacity of wild‐type GPC‐2 to activate receptor signaling on chondrocytes, thereby mediating a pro‐anabolic, chondrogenic, activity. Overexpression of GCP‐2‐T improved cartilage integrity and reduced pain in experimental osteoarthritis in mice without inducing local accumulation of neutrophils. Abstract : Osteoarthritis, which is the most common cause of disability, leads to breakdown of the articular cartilage and causes joint pain and loss of mobility; however, we do not have a pharmacological treatment for arresting or reverting its course.